Students' Numeracy Ability on Data Elements and Data Uncertainty - Muhammad Ilham; Nikmah Nurvicalesti (Jurnal Inovasi Matematika, 2025)
Numeracy skills are a person's skills to formulate, communicate, apply and use mathematical concepts in various situations to solve real-life problems. The purpose of this study is to determine the effectiveness of students' numeracy skills on data elements and data uncertainty. he research employs quantitative descriptive approaches. The sample for this study consisted of 32 seventh-grade students from a public junior high school in Belitang. This research's data collection techniques included written tests and documentation. The questions given consist of 4 questions with data presentation material. The test instrument is designed based on numeracy ability indicators and has met valid and reliable criteria. Data analysis in this research used a one-sample z test with the prerequisite of the shapiro-wilk normality test analysis. The results of the hypothesis test with a significance level of 5% stated that the p-value (0.0705 > 0.025), this can be seen that there is effectiveness in students' numeracy abilities in data elements and data uncertainty at class VII.